The Role of Community Counselors in Diversion Efforts Between Child Offenders and Victims - Rudi Suwardana (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Diversion is a concept in criminal law that refers to efforts to move cases of minor crimes or first-time offenders toward lighter or alternative legal proceedings than traditional criminal courts. The main aim of diversion is to prevent social stigmatization associated with the criminal justice process, provide criminals with an opportunity to improve their behavior, and reduce the burden on the criminal justice system. Criminal responsibility for children must be considered with the principles of caution and sensitivity because children generally have lower physical, emotional and cognitive maturity compared to adults. The main aim of criminal responsibility for children is to provide sanctions that are appropriate to the child's needs for rehabilitation and development, not just imposing correctional punishments. The role of community counselors (PK) in diversion efforts is very important in developing a more inclusive, rehabilitative and community-based approach to law enforcement. PK is responsible for conducting evaluations and assessments of individuals involved in legal violations. They collect information about social background, family environment, mental health, education, and other factors that may contribute to offending behavior. This evaluation helps PK understand individual needs holistically. Even though diversification efforts are an approach that is considered more holistic and inclusive, community counselors (PK) also face several obstacles that may affect the implementation of diversion, including limited resources in terms of personnel, budget, or infrastructure needed to provide comprehensive and effective services to individuals involved in the offence. Keywords: the role of community mentors in diversion efforts.